High resolution isotopic ages for the early Miocene "Patagoniense" transgression in Southwest Patagonia: Stratigraphic implications - Cuitiño, José Ignacio (2012)
The classical marine Patagoniense succession at Lago Argentino, southwestern Patagonia (Argentina), known as Estancia 25 de Mayo Formation, was dated by radiometric U-Pb on zircon grains from pyroclastic rocks and 87Sr/ 86Sr ratio on calcitic oyster shells. U-Pb data yielded an age of 19.14 Ma for the lower portion of the Patagoniense succession and 18.85 Ma for the lowermost part of the overlying Santa Cruz Formation. 87Sr/ 86Sr data yielded ages ranging from 20.05 Ma at the lower part and 19.1 Ma for the upper portion of the Estancia 25 de Mayo Formation, in good agreement with respect to the U-Pb results. Our results constrain the age of these beds entirely into the early Miocene Burdigalian stage, and locally into the Superpatagoniense stage. Correlation with other Patagoniense units in Santa Cruz, especially in the westernmost parts of the Austral Basin, reveals the existence of a shallow and extended sea, and lack of correlation with global sea-level highstands suggests a local Andean tectonic overprint as the cause of the sea level rise.